2013
DOI: 10.1039/c3nj00693j
|View full text |Cite
|
Sign up to set email alerts
|

Liberation of methyl acrylate from metallalactone complexes via M–O ring opening (M = Ni, Pd) with methylation agents

Abstract: Ring opening of various nickela-and palladalactones induced by the cleavage of the M-O bond by methyl trifluoromethanesulfonate (MeOTf) and methyl iodide (MeI) is examined. Experimental evidence supports the mechanism of ring opening by the alkylating agent followed by b-H elimination leading to methyl acrylate and a metal-hydride species. MeOTf shows by far higher efficiency in the lactone ring opening than any other methylating agent including the previously reported methyl iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
(11 reference statements)
1
29
0
Order By: Relevance
“…Scheme 24. Nickelalactone ring opening triggered by methyl electrophiles [90,91] Limbach and Hofmann reported a comprehensive theoretical study on the mechanism of the nickelmediated synthesis of methyl acrylate from ethylene, CO 2 and methyl iodide [92]. DFT calculations revealed an SN 2 -type mechanism for the alkylation of the carboxylate ligand, which explain the experimental observations gathered by the groups of Rieger and Kühn.…”
Section: Scheme 23supporting
confidence: 52%
“…Scheme 24. Nickelalactone ring opening triggered by methyl electrophiles [90,91] Limbach and Hofmann reported a comprehensive theoretical study on the mechanism of the nickelmediated synthesis of methyl acrylate from ethylene, CO 2 and methyl iodide [92]. DFT calculations revealed an SN 2 -type mechanism for the alkylation of the carboxylate ligand, which explain the experimental observations gathered by the groups of Rieger and Kühn.…”
Section: Scheme 23supporting
confidence: 52%
“…Importantly, DFT calculations revealed that the rate-determining step corresponded to the addition of methyl iodide. In line with this notion, the authors found that the inclusion of methyl triflate (MeOTf) significantly enhanced the rate of the reaction [91]. Unlike the use of methyl iodide, the reaction of MeOTf turned out to be particularly efficient with dppe, dppp, or even dppb, whereas the employment of TMEDA failed to provide the targeted methyl acrylate.…”
Section: Carboxylation Of Ethylene With Co 2 En Route To Acrylate Dermentioning
confidence: 82%
“…Scheme 24 Nickelalactone ring opening triggered by methyl electrophiles [90,91] (c-nickelalactone), in which the Lewis acid is coordinated to the carboxylate fragment, ultimately leading to a four-membered nickelacycle via b-hydride elimination and subsequent migratory insertion (Scheme 25). The latter species underwent formation of acrylate Ni(0) p-complexes upon addition of a base such as BTPP [tert-butyliminotri(pyrrolidino)phosphorane] or DBU.…”
Section: = I Otfmentioning
confidence: 99%
“…However, later considerations revealed that the release of acrylic acid is also thermodynamically unfavored [54,55]. As a result, the cleavage of nickelalactones by various electrophiles such as alkyl halides (see, e.g., [56][57][58]), protons (see, e.g., [59,60]), and Lewis acids (see, e.g., [60,61]) has been studied, but a catalytic process could not be established until a recent report by Limbach and co-workers [62].…”
Section: Nickel-catalyzed Reactionsmentioning
confidence: 99%